Nilai Etika Konselor dalam Membangun Interaksi Efektif antara Konselor dan Konseli - Akhir Pardamean Harahap; Ummi Nurhasanah; Adam Adhitya Perdana; Ridho; Muhammad Irvan Anggana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to investigate ethical values ​​that are important in building effective interactions between counselors and counselees in a counseling context. The research method used is literature study, by collecting data from various relevant literature. The data collection process involves reading, studying, examining and carefully examining hadith texts and related literature. Data analysis was carried out by organizing data into groups based on emerging themes, referring to the Lexy approach and content analysis. The research results show that ethics in counseling is a moral foundation that guides the behavior and interactions of counselors with their clients. The principles of counseling ethics, such as respecting human dignity and human rights, maintaining the confidentiality of client information, and promoting social justice, are essential to the practice of counseling. Counselors are expected to understand, internalize, and implement these ethical values ​​in order to help clients effectively and ensure that counseling takes place in a safe and trustworthy atmosphere. In addition, ethical values ​​that are important for a counselor in building a meaningful and effective relationship with clients include autonomy, not violating a code of ethics, fairness, and loyalty. Personal values ​​such as having faith and devotion to God Almighty, respecting human values ​​and individuality, and showing integrity and stability of personality also help strengthen the counselor-counselee relationship. By understanding, internalizing, and implementing these ethical and personal values, a counselor can build meaningful and effective relationships with his counselees, and carry out his duties and functions well at school. It is hoped that this research will provide an in-depth understanding of the ethical values ​​that are important in counseling practice. Keywords: Counselor Ethical Values, Interaction The purpose of this research is to investigate ethical values ​​that are important in building effective interactions between counselors and counselees in a counseling context. The research method used is literature study, by collecting data from various relevant literature. The data collection process involves reading, studying, examining and carefully examining hadith texts and related literature. Data analysis was carried out by organizing data into groups based on emerging themes, referring to the Lexy approach and content analysis. The research results show that ethics in counseling is a moral foundation that guides the behavior and interactions of counselors with their clients. The principles of counseling ethics, such as respecting human dignity and human rights, maintaining the confidentiality of client information, and promoting social justice, are essential to the practice of counseling. Counselors are expected to understand, internalize, and implement these ethical values ​​in order to help clients effectively and ensure that counseling takes place in a safe and trustworthy atmosphere. In addition, ethical values ​​that are important for a counselor in building a meaningful and effective relationship with clients include autonomy, not violating a code of ethics, fairness, and loyalty. Personal values ​​such as having faith and devotion to God Almighty, respecting human values ​​and individuality, and showing integrity and stability of personality also help strengthen the counselor-counselee relationship. By understanding, internalizing, and implementing these ethical and personal values, a counselor can build meaningful and effective relationships with his counselees, and carry out his duties and functions well at school. It is hoped that this research will provide an in-depth understanding of the ethical values ​​that are important in counseling practice.